PENGARUH FINANCIAL DISTRESS, UKURAN PERUSAHAAN DAN KEBIJAKAN HUTANG TERHADAP TAX AVOIDANCE DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Jane Onoyi, Nona; Kurniawati, Ely; Yantri, One; Titik Windayati, Diana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study used audit quality as an moderating variable to examine the effect of financial distress, firm size and debt policy on tax avoidance. Tax avoidance is proxied by the cash effective tax rate, financial distress is proxied by the Z-Score model, firm size is proxied by the natural logarithm of assets, debt policy is proxied by the debt to asset ratio and Audit quality is proxied by the big four Public Accounting Firm (KAP). The population in this research is energy companies listed on the Indonesia Stock Exchange in 2016-2020 with a total of 32 companies. The research sample consisted of 11 companies obtained by using purposive sampling technique. The analysis technique used is linear regression with a moderation model. The results showed that partially financial distress, firm size and debt policy have a significant effect on tax avoidance. While audit quality is not able to moderate the effect of financial distress, firm size and debt policy significantly affect tax avoidance. However, audit quality can strengthen the effect of financial distress, firm size and debt policy on tax avoidance. This situation is a yellow light and even a red light for the government. The government needs to review tax regulations and provide stimulus to taxpayers so that tax revenues increase. For taxpayers, it is necessary to be more careful in carrying out tax avoidance so as not to be included in tax audits and courts as a result of carrying out excessive tax avoidance.Keywords: Financial Distress, Firm Size, Debt Policy, Audit Quality, Tax Avoidance